Aktualisasi Nilai-Nilai Inklusif di Sekolah Multiagama, Perspektif Pendidikan Multikultural - Zanki, Amir Basari; Indriani, Indriani; Takunas, Rusli; Nursyam, Nursyam; Zanki, Harits Azmi; Pahude, Jupriadi J. (Paedagogie, 2026)
This study aims to examine the actualization of inclusive values in multi-religious schools from a multicultural education perspective. A qualitative approach with a library research method was employed. Data were collected through a systematic literature search of relevant scholarly journal articles and academic books, selected using inclusion and exclusion criteria. Data analysis was conducted using content analysis and thematic analysis to identify key concepts, patterns, and major themes related to the implementation of inclusive values. The findings indicate that inclusive values are effectively actualized through the integration of values into learning processes, the strengthening of teachers’ roles as agents of multicultural education, and the development of dialogical and equitable school culture and policies. This study concludes that multicultural education serves as a practical framework for building an inclusive educational ecosystem in multi-religious schools rather than merely a normative discourse.